Trace metals accumulation on modern sediments from Po river prodelta, North Adriatic Sea. (February 2022) - Riminucci, Francesco; Funari, Valerio; Ravaioli, Mariangela; Capotondi, Lucilla
Abstract: Trace Metals (TMs: Pb, Zn, Cu, Cr, Cd, and Ni), major elements (Al and Fe) and radionuclides ( 210 Pb/ 137 Cs) investigations on EL-C01 sediment core provides new information on sedimentary regime and anthropogenic impacts during the last 175 years in the Po river prodelta area. The results allow to identify some TMs/Al peak in the upper part of the core, likely related to the major flood events of the Po river during the XXth century. Sediments deposited after the year 1900 exhibit a gradual increase of some TMs concentrations compared to pre-industrial era values. In particular, Pb, Zn, and Cu high contents are detected after the World War II and during the "Italian Economic Miracle" period. The decrease of heavy metal (Zn and Pb) contents from the second half of the 1980s is probably the effect of the Italian Law 319/76 and anti-pollution environmental policies concerning industrial and urban emitters. Highlights: Po river prodelta 175 yr environmental history reconstructed from a sediment core Trace metal peaks identify Po river major flood events during the XXth century Cu, Pb, and Zn trends relate to the economic/industrial Italian history Pre-industrial Pb and Zn concentrations of 31 and 91 mg kg −1 respectively